Newborn Critical Congenital Heart Disease Screening Using Pulse Oximetry: Value and Unique Challenges in Developing Regions - Lisa A. Hom; Gerard R. Martin (MDPI AG, 2020)
Newborn screening for critical congenital heart disease (CCHD) is recommended for implementation in many developed countries as the standard of care. Efforts to implement this point of care screen in developing regions face unique barriers, and present important opportunities. The First Pan-African Newborn Screening Conference, held in Rabat in June 2019, incorporated a workshop dedicated specifically to identifying and discussing CCHD screening issues in the Middle East Northern Africa (MENA) region. The issues explored may be beneficial as part of the greater discussion of CCHD screening's growing importance in developing regions around the world. Screening experts presented education and lessons learned from previous CCHD implementations, including a hands-on technical demonstration of CCHD screening. Children's HeartLink, The Newborn Foundation, and Children's National Hospital each presented on their experiences working with teams and pilot projects from around the world. Experience in implementation from Children's Hospital Marrakesh was presented and highlighted some of the unique findings, challenges, and experiences of screening in Morocco. As developing regions investigate the implementation of CCHD screening using pulse oximetry either as part of research studies, pilots, regional studies, or as part of a nationally supported program, data to inform policymakers on the benefits of screening and specific needs for infrastructure development and resources are essential. This special issue contains initial lessons learned on newborn CCHD screening from a select number of developing countries, including Saudi Arabia and Morocco and regions such as Latin America.